The Effectiveness of Learning Media Folklore Text of North Sumatera Based on Blended Learning by 10th Grade Students of Vocational High SchoolHarapan Mekar-1 Medan - Tri Indah Prasasti; Mutsyuhito Solin; Wisman Hadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aim of the study is to find out the effectiveness of learning media folklore text of North Sumatra based on blended learning. This study used research and development of learning media based on blended learning takes the form of online, offline and face-to-face learning media. The result of the study Learning outcomes in the folklore text material of 10th Grade students of Vocational High School Harapan Mekar-1 Medan after using learning media based on blended learning are in the category of "very good" with an average value of 82.81 and the average value before using learning media based on blended learning of 67.65 which is in the "good" category. This proves that student learning outcomes in writing folklore text material using blended learning based learning media is higher with the difference in percentage from pretest to posttest is 15,16.